Initial experience with the Scepter Mini catheter for the embolization of vascular malformations in the pediatric population. Issue 4 (August 2022) - Matsoukas, Stavros; Bageac, Devin; Yaeger, Kurt; Berenstein, Alejandro; T Fifi, Johanna; Shigematsu, Tomoyoshi
Background: Achieving distal access and flow control are of significant importance for the treatment of intracerebral arteriovenous shunting lesions. The Scepter Mini catheter is a low-profile, dual-lumen balloon catheter, designed to provide navigability in small-caliber, tortuous intracranial vessels. Objective: To describe the initial experience of the Scepter Mini catheter in the treatment of pediatric arteriovenous malformations and fistulas. Methods: A single-institution, retrospective chart review identified all consecutive uses of the Scepter Mini catheter for endovascular embolization of vascular malformations in the pediatric population. Results: Three different arterial pedicles were embolized with the Scepter Mini catheter in two different patients. One patient was diagnosed with a vein of Galen malformation that had undergone multiple treatments and the other with a torcular dural arteriovenous fistula. All cases encompassed quite challenging tortuosity of small-caliber feeders which prevented the use of another microcatheter. The Scepter Mini catheter navigated into feeding arteries of diameters 0.65, 1.9, and 1.25 mm, and its balloon was inflated to achieve excellent blood flow control. Total obliteration (100%) of the shunting lesion was achieved in both cases. No reflux, pedicle rupture or other untoward effects were observed. Both patients had an uneventful recovery. Conclusion: The Scepter Mini catheter afforded fast and safe distal access, flow control, and treatment of arteriovenous malformations in this initial pediatric cohort. The catheter's low profile and easy navigability should support its use in tortuous and small arterial feeders, especially in the pediatric population.